PERIODISMO CRIMINALÍSTICO Y SU EFECTO EN LAS INVESTIGACIONES DE LA POLICÍA NACIONAL EN EL CANTÓN PUEBLOVIEJO, AÑO 2022. - Flores Cedillo, Kenya Maday (2022)
This research project, whose main objective is to analyze the effects of criminal journalism in the investigations of the National Police of the Puebloviejo canton in the year 2022 and specific objectives; to substantiate through theoretical foundations the influence of criminal journalism in the police investigations of the Puebloviejo canton; determine the increase in criminal acts and fatal crimes through the investigations of the National Police within the Puebloviejo canton; propose through criminal journalism within the investigations of the National Police and the Community Service of the Puebloviejo canton, the resolution of cases, for the benefit of citizens; whose problem was addressed from a mixed, quantitative - qualitative, inductive - predictive investigation, explaining the nature of the phenomenon to carry out the proposals for action on the described reality. Forty members in active service with exercise within the Puebloviejo canton in the year 2022 were taken into consideration as a population.